2014
DOI: 10.1177/0956797614541990
|View full text |Cite
|
Sign up to set email alerts
|

Practice Does Not Make Perfect

Abstract: The relative importance of nature and nurture for various forms of expertise has been intensely debated. Music proficiency is viewed as a general model for expertise, and associations between deliberate practice and music proficiency have been interpreted as supporting the prevailing idea that long-term deliberate practice inevitably results in increased music ability. Here, we examined the associations (rs = .18-.36) between music practice and music ability (rhythm, melody, and pitch discrimination) in 10,500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(100 citation statements)
references
References 33 publications
7
92
0
1
Order By: Relevance
“…Individual differences in personality or motivation to practice may influence who chooses to engage in music training and who plays video games (Corrigall et al, 2013;Mosing et al, 2014). In our case, the gamers had personalities that contrasted with the typical personality profile for musicians, although this could be the result of gender differences between our groups.…”
Section: Discussionmentioning
confidence: 72%
“…Individual differences in personality or motivation to practice may influence who chooses to engage in music training and who plays video games (Corrigall et al, 2013;Mosing et al, 2014). In our case, the gamers had personalities that contrasted with the typical personality profile for musicians, although this could be the result of gender differences between our groups.…”
Section: Discussionmentioning
confidence: 72%
“…In each case, we found that the observed associations were essentially driven by pleiotropies, common genetic influences, rather than by causal effects of practicing on a trait or vice‐versa. Indeed, we have found that genetic factors have a substantial influence on practicing behaviour itself 11. Evidence has also been found for gene–environment interaction, which showed that genetic effects on music accomplishment were stronger for those who had engaged in music practice, that is, that innate properties attract people with higher potential to practice more 12.…”
Section: Introductionmentioning
confidence: 61%
“…In principle, these diverse associations could reflect various underlying causal scenarios. However, we have recently used twin modelling to study the genetic architecture of associations between musical training on the one hand and personality 3, intelligence 10 and musical discrimination ability 11 on the other hand. In each case, we found that the observed associations were essentially driven by pleiotropies, common genetic influences, rather than by causal effects of practicing on a trait or vice‐versa.…”
Section: Introductionmentioning
confidence: 99%
“…In both neuroscience and psychology, ideas about musical talent are further complicated. Scholars such as Hambrick and Tucker-Drobb (2014) and Mosing et al (2014Mosing et al ( : 1800, for example, argue that a mix between genetic and environmental factors affect a person's capacity to realise talent (see also Stetka 2014). Similarly, neuroscientist Gary Marcus' (2012) popular science book on musical learning distinguishes between "music instinct" (a myth) on the one hand and other types of "talent" (a valid concept), on the other (Marcus 2012: 9).…”
Section: Talent (And Its Gendering)mentioning
confidence: 99%